Language Learning Autonomy among Jordanian EFL University Students - Misarah Zreagat; Sarjit Kaur (UiTM Publisher, 2012)
Autonomy in language learning has gained prominence due to the preference for learner-centred styles. An implementation of autonomy in learning should be preceded by an investigation of learners' readiness for autonomous learning, taking into account the cultural differences of different communities. This article reports findings about the perceived learning autonomy among EFL university students in Yarmouk University in Jordan. 154 students taking English proficiency based courses and five lecturers teaching these courses took part in the research. Both quantitative and qualitative methods were used to conduct the research. A 43-item questionnaire adapted from Chan, Spratt & Humphreys (2002) was used to collect the quantitative data while semi-structured interviews were conducted with the students and their lecturers. The findings revealed that teaching of English is still highly teacher-centred in Jordanian university classrooms. In relation to the autonomy construct, the results show that although Jordanian EFL university students feel that they are, somehow responsible for autonomous learning, they do not possess the ability to act autonomously nor do they embark on engaging in any autonomous activities. The implications of this study suggest that policy makers in Jordan need to pay more attention to the process of teaching English in Jordanian universities.